Penyuluhan Pembuatan Pupuk Organik Cair (POC) Dari Limbah Sayur di Dusun Jatisari, Desa Ngajum, Kabupaten Malang - Agustin, Ine Aulia; Pawestriningtyas, Husnatul Kholivia; Lestari, Ludy Wiji; Al Aziz, Sandy; Rahmat, Fathur; Gafur, Abdul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Vegetable organic waste can cause an unpleasant odour and pollute the environment without proper management. One alternative to handling this waste is to process it into liquid organic fertilizer. Liquid organic fertilizer (POC) is a solution resulting from the decomposition of plant residues and animal manure that contains more than one nutrient needed by plants. The purpose of holding this counselling is to provide knowledge to homemakers in the RT.03 RW.13 Jatisari Hamlet, Ngajum Village, that vegetable waste can be processed into liquid organic fertilizer (POC). Counselling activities were carried out face- to-face with 25 extension participants. Counselling was carried out through 3 stages: giving material for 20 minutes, training on making liquid organic fertilizer from vegetable waste and distributing fermented fertilizer for two weeks to counselling participants. The fermentation process in the manufacture of liquid organic fertilizer uses Effective Microorganisms (EM4) bio activators which can speed up the composting process. The evaluation method is the method without analysis by looking at the number of participants who have understood how to make Liquid Organic Fertilizer (POC) step by step. The extension activities found that the community already understood the importance of managing vegetable waste and how to make liquid organic fertilizer from it.